Quality and Accreditation Standards in Physical Education Colleges in Libyan Public Universities from the Point of View of Executive Management - Hamouda, Ashraf; Boukari , Samia; Attia, Ahmed; Mhenni, Thouraya; Al-Kilanii, Abdul Bari; Gaied Chortane, Sabri; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2024)
This research aims to identify quality standards in physical education colleges in Libyan public universities, in relation with educational literature and the most important drivers of interest in implementing the quality assurance and accreditation system in universities. To achieve the research objectives, the descriptive method using the survey method was used. The sample consisted of ninety (90) individuals from the executive management in the colleges, thirty-eight (38) quality coordinators in the departments in the colleges, and fifty-two (52) department heads. In this research, a questionnaire form was applied that included four (4) axes and fifty-eight (58) statements, and statistical treatments were applied using the SPSS version 2020 software. The most important results of this study are that the college sets its goals based on its vision and mission in line with the needs of society through effective strategies announced in a public place to be a reference for evaluating progress in the college. It was also concluded that the college’s human resources (trainers and administrators) are sufficient to perform the tasks assigned to them through the work of committees and work teams and writing periodic reports on achievements, work performance, and development. The College Council also makes its decisions according to clear and specific tasks with the formation of distinguished work teams. One of the most important recommendations of the research is the college council’s approval of formulating the college’s vision and mission, the need to emphasize the presence of a quality and accreditation office in every college and unit for every department in the organizational structure of physical education colleges in Libyan public universities, and the necessity of developing a guideline for quality standards for accreditation in physical education colleges in Libyan public universities.